Long Non-coding RNA AK025387 Promotes Cell Migration and Invasion of Gastric Cancer - Sun, Yi-Yuan; Zhang, Hui; Ma, Ran-Ran; Zhang, Guo-Hao; Tian, Ya-Ru; Liu, Lei; Liu, Lin; Gao, Peng (Frontiers in Oncology, 2020)
Gastric cancer is one of the most common cancers in the world and long noncoding RNAs (lncRNAs) play a crucial role in proliferation, metastasis and invasion of gastric cancer. However, there are very few researches focusing on the effects of lncRNAs on metastatic gastric cancer. In this research, we identify one kind of lncRNA, called AK025387, which is highly expressed in metastatic gastric cancer samples compared with non-metastatic gastric cancer samples. The expression of AK025387 is significantly positively correlated with lymph node metastasis. The in situ hybridization demonstrates that AK025387 is located in both nucleus and cytoplasm, but mostly in cytoplasm. AK025387 promotes gastric cancer cells migratory and invasive ability, but it inhibits apoptosis in vitro. Further, AK025387 regulates Raf-1, MEK and ERK and is involved in MAPK signaling pathway to perform its biological functions. We conclude that AK025387 is highly expressed in metastatic gastric cancer and its biological functions suggest the potential of AK025387 to be a biomarker of metastatic gastric cancer.